Aortic Dissection and Renal Failure in a Patient with Severe Hypothyroidism - Brooke, Valerie (Hindawi Publishing Corporation, 2012)
Acute aortic dissection (AAD) is a life-threatening condition associated with high morbidity and mortality. The most important recognized acquired cause that leads to dissection is chronic arterial hypertension. With respect to the anuria and renal failure, aortic dissection is not something that is always considered and is still not a very common presentation unless both renal arteries come off the false lumen of the dissection. However, when present, preoperative renal failure in patients with acute type B dissection has been noted to be an independent predictor of mortality. Early recognition and diagnosis is the key and as noted by previous studies as well, almost a third of these patients are initially worked up for other causes until later when they are diagnosed with aortic dissection. Here we present a case of a patient presenting with severe hypothyroidism, long-standing hypertension, and anuria. Through the case, we highlight the importance of having aortic dissection as an important differential in patients presenting with anuria who have a long standing history of uncontrolled hypertension. Pathophysiology relating to severe hypothyroidism-induced renal dysfunction is also discussed.